T cell activation and antigen presentation in human thyroid autoimmunity. - Feldmann, M; Dayan, C; Rapoport, B; Londei, M (1992)
In 1983, a hypothesis concerning the relevance of class II expression and antigen presentation to the induction and maintenance of endocrine autoimmunity was published. This article reviews the evidence that has been marshalled to support this concept, both in man, chiefly in Graves' disease, and in murine systems. New data concerning the multiplicity of thyroid autoantigens recognized by in vivo activated thyroid infiltrating T cells are compatible with this concept since the thyroid epithelial cells are the source of these antigens. Whether other autoimmune diseases also employ the same mechanism remains to be ascertained, as does the initial trigger for the autoimmune process.